2020
DOI: 10.3389/fimmu.2020.586889
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of IL-22 Bioactivity and IL-22-Positive Cells in Grass Carp Ctenopharyngodon idella

Abstract: Interleukin (IL)-22 plays an important role in regulating inflammation and clearance of infectious pathogens. IL-22 homologs have been discovered in fish, but the functions and sources of IL-22 have not been fully characterized. In this study, an IL-22 homolog was identified in grass carp and its bioactivities were investigated. The grass carp IL-22 was constitutively expressed in tissues, with the highest expression detected in the gills and hindgut. It was upregulated in the spleen after infection with Flavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 50 publications
(107 reference statements)
0
5
0
Order By: Relevance
“…IL-22 is conserved in zebrafish (Igawa et al, 2006;Siupka et al, 2014) and also found in other fish species (Corripio-Miyar et al, 2009;Monte et al, 2011;Costa et al, 2013;Yang et al, 2020). In zebrafish, expression of IL-22 was seen in the intestine and gill at baseline and increased after a challenge with TLR agonists (LPS/Poly I:C) (Siupka et al, 2014).…”
Section: Function Of Interleukin 22 In Gut Microbial Compositionmentioning
confidence: 78%
“…IL-22 is conserved in zebrafish (Igawa et al, 2006;Siupka et al, 2014) and also found in other fish species (Corripio-Miyar et al, 2009;Monte et al, 2011;Costa et al, 2013;Yang et al, 2020). In zebrafish, expression of IL-22 was seen in the intestine and gill at baseline and increased after a challenge with TLR agonists (LPS/Poly I:C) (Siupka et al, 2014).…”
Section: Function Of Interleukin 22 In Gut Microbial Compositionmentioning
confidence: 78%
“…In previous studies on IL-22RA1 KO mice, the induction of Bcl2115 , Nupr1 , and Chac1 transcripts was suggested to be associated with the IL-22/IL-22RA1 axis via STAT3 activation ( 52 ). Furthermore, a recombinant protein-based functional study on teleost IL-22 revealed that recombinant IL-22 can induce defb and hamp expression in rainbow trout ( 29 ), il1b expression in grass carp ( 56 ), and il22bp and hamp expression in mandarin fish ( 33 ). Thus, the phenotypic characteristics of IL-22-KO medaka showed several similarities with those reported in previous studies on the IL-22 induction abilities in mammals and teleosts.…”
Section: Discussionmentioning
confidence: 99%
“…Gene syntenic relationships were analyzed using the Ensembl website (https://asia.ensembl. org/index.html) as previous studies on the IL-10 family [15,[33][34][35]. The NCBI genome databases, BioEdit and Ultra-Edit-32 programs, were used to analyze IL-10 family gene organizations in spotted sea bass.…”
Section: 3mentioning
confidence: 99%